Pengembangan Model Pelatihan Persiapan Persalinan untuk Ibu Hamil dan Pasangannya di Kabupaten Bandung - Ina Yulianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2015)
The research’s aim was to develop model of training for childbirth preparation and parenting. The research was conducted at Women Centre Care Clinic in Panjalu Village in Bandung. The research and development used was mix method approach and indicated tha there were problems of parents readiness to face the changes of childbith and newborn baby care, ineffective of current antennal class. The learning strategy developed produced active and enjoyable learning, stimulated learner and facilitator enthusiasm. Learning products were useful for learning process, improved the participants’ intellectual and mental capacity in order to conduct the parents’ roles in childbirth process. Learning process provided conducive situation, built the parents responsibility to provide mother and father task in childbirth and newborn baby care